2017
DOI: 10.1214/16-aos1452
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the number of factors from singular values of a large sample auto-covariance matrix

Abstract: Identifying the number of factors in a high-dimensional factor model has attracted much attention in recent years and a general solution to the problem is still lacking. A promising ratio estimator based on the singular values of the lagged autocovariance matrix has been recently proposed in the literature and is shown to have a good performance under some specific assumption on the strength of the factors. Inspired by this ratio estimator and as a first main contribution, this paper proposes a complete theory… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 26 publications
0
45
0
Order By: Relevance
“…observation, such as establishment of phase transition phenomena, characterization of limiting distribution of extreme eigenvalues, establishment of CLT for linear spectral statistics, estimation of spectra of population covariance, to the setting of time-dependent data. Significant progress related to phase transition phenomena for singular values of sample autocovariances has been made in [108] and [109]. A method for estimating the joint spectrum of coefficient matrices of a class of ARMA processes has been developed in [110].…”
Section: Concluding Discussionmentioning
confidence: 99%
“…observation, such as establishment of phase transition phenomena, characterization of limiting distribution of extreme eigenvalues, establishment of CLT for linear spectral statistics, estimation of spectra of population covariance, to the setting of time-dependent data. Significant progress related to phase transition phenomena for singular values of sample autocovariances has been made in [108] and [109]. A method for estimating the joint spectrum of coefficient matrices of a class of ARMA processes has been developed in [110].…”
Section: Concluding Discussionmentioning
confidence: 99%
“…Many methods have been developed to determine the number of principal components for conventional PCA, such as the ratio estimator (Lam and Yao, 2012;Li et al, 2017), the information criteria approaches Ng, 2002, 2007), the distribution-based approach (Choi et al, 2014) or just by the amount of variance explained (e.g., 90%). Although these methods can be easily extended to the current sKPCA framework, we have found that none of them works optimally in the subsequent association tests, which is our main goal in this paper.…”
Section: The Choice Of Skpca Parametersmentioning
confidence: 99%
“…There are many developed methods to determine the number of principal components for conventional PCA, such as the ratio estimator [Lam and Yao, 2012;Li et al, 2017b], the information criteria approaches Ng, 2002, 2007], the distribution-based approach [Choi et al, 2014] or just by the amount of variance explained (e.g. 80%) or the average variance explained.…”
Section: The Choice Of Skpca Parametersmentioning
confidence: 99%